Bibliometric Analysis of the Development of Information Literacy Publications in ASEAN Countries Indexed by the Lens Database - Luthfiyah Eka Yani; Danang Dwijo Kangko; Indah Kurnianingsih; Aya Yahya Maulana (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: Information literacy plays a vital role in supporting education, research, and informed decision-making in the digital era. In the context of ASEAN countries, the development and dissemination of research on information literacy contribute to regional knowledge-sharing and capacity building. However, comprehensive mapping of scholarly output on this subject in ASEAN remains limited, especially those indexed in global academic databases.